Pemisahan Unsur Samarium dan Yttrium dari Mineral Tanah Jarang dengan Teknik Membran Cair Berpendukung (Supported Liquid Membrane) - Amin, Amri (Jurnal Rekayasa Kimia & Lingkungan, 2009)
he increasing use of rare earth elements in high technology industries needs to be supported by developmental work for the separation of elements. The research objective is fiercely attracting and challenging considering the similarity of bath physical and chemical properties among these elements. The rate separation of samarium and yttrium elements using supported liquid membrane has been studied. Polytetrafluoroethylene (PTFE) with pore size of 0.45 m has been used as the membrane and di(2-ethylhexyl) phosphate (D2EHP) in hexane has been used as a carrier and nitric acid solution has been used as receiving phase. Result of experiments showed that the best separation rate of samarium and yttrium elements could be obtained at feeding phase of pH 3.0, di(2-ethylhexyl) phosphate (D2EHP) concentration of 0.3 M, agitation rate of 700 rpm, agitation time of 2 hours, and nitric acid and its solution concentrations of 1.0 M and 0.1 M, respectively. At this condition, separation rates of samarium and yttrium were 64.4 and 67.6%, respectively. Keywords: liquid membrane, rare earth elements, samarium, yttrium